A escola como espaço de formação pedagógica permanente do professor - Figueiredo, Aureny Gomes Coelho (2012)
This paper is the result of some research related to the Post-graduation Master’s Program in Education at the Human and Social Sciences Institute (ICHS), linked to the Mato Grosso Federal University (UFMT), Rondonopolis University Campus (CUR). The question that guided such study was the following one: Has the continuing education offered in the school contributed to the improvement of the teacher’s pedagogical practice? To investigate whether the Secretariat policy encouraged the school to offer a training course in its Political Pedagogical Project. Besides that, to examine which analysis the teachers make of such training carried out in their school was the main goal of this study. Reaching such answer was the main goal of this investigation. While carrying out the research, the instruments for data collection were questionnaires, semi-structured interviews with teachers, pedagogical coordinator and director; documental analysis and observation of the continuing education offered in the school. The investigation followed two phases, and, at first, 63 teachers of 21 municipal schools were the research subjects; at a later stage, a school was selected to be the locus of the research, and seven teachers became the subjects of the investigation. It is needed to say that four of them were actual teachers in the classroom, two were in the pedagogical coordination and one in the school board. The investigation was based on theoretical backgrounds provided by qualitative research, following thoughts and ideas by Minayo (2010), Lüdke and André (2007), André (2005 and 2009), Ghedin and Franco (2008), among others. Studies by Freire (2004 and 1991), Carvalho (2005, 2006 and 2010),Franco (2008), Freitas (2004), Canário (2006), Imbérnon (2009), Nóvoa (1999 and 2009) and others were taken into account as well, for the body of conceptual discussions and reflections and the comprehensive analysis of the data collected during the research. The results of the research revealed that the teachers consider their own education the cornerstone in the improvement of their practice. However, it was also clear that the teacher’s education developed in the school needs to be reconsidered and questioned regarding what is somewhat notorious, as policy, and what the school has actually been able to accomplish when it comes to the continuing education for the teachers.